Pentraxin 3(PTX 3): An Endogenous Modulator of the Inflammatory Response - P. Kunes; Z. Holubcova; M. Kolackova; J. Krejsek (Hindawi Limited, 2012)
Inflammatory or anti-inflammatory? That is the question as far as the acute-phase response and its mediators, the pentraxins, are concerned. Only some ten years ago, the classical or short pentraxin C-reactive protein and the newly discovered long pentraxin PTX3 were considered to exert most of the detrimental effects of acute inflammation, whether microbial or sterile in origin. However, accumulating evidence suggests an at least dichotomous, context-dependent outcome attributable to the pentraxins, if not a straightforward anti-inflammatory nature of the acute-phase response. This paper is focused on the inherent effects of pentraxin 3 in inflammatory responses, mainly in coronary artery disease and in Aspergillus fumigatus infection. Both are examples of inflammatory reactions in which PTX3 is substantially involved; the former sterile, the latter infectious in origin. Apart from different inducing noxae, similarities in the pathogenesis of the two are striking. All the same, the introductory question still persists: is the ultimate impact of PTX3 in these conditions inflammatory or anti-inflammatory, paradoxical as the latter might appear? We try to provide an answer such as it emerges in the light of recent findings.